Bibliometric Analysis: Implementation of Islamic Boarding School Entrepreneurship Education in Indonesia - Rachma Putri Kasimbara; Ulfah Umurohmi; Ahmad Afandi; Iskandar, Iskandar (Mudir : Jurnal Manajemen Pendidikan, 2024)
Enterprise instruction is progressively being coordinates into the educational programs of pesantren (Islamic boarding schools) in Indonesia to plan understudies for financial freedom and societal commitments. This consider utilizes bibliometric investigation to investigate the patterns, designs, and commitments of investigate on enterprise instruction execution in pesantren from 2010 to 2020. The examination uncovers a critical increment in distributions over time, essentially comprising of diary articles, showing developing insightful intrigued within the theme. Collaboration between pesantren analysts, instructive educate, and worldwide researchers is outstanding, improving the talk on business enterprise instruction. Recognized investigate subjects incorporate instructing strategies, financial impacts, program victory variables, and collaboration designs. This bibliometric investigation gives important bits of knowledge for policymakers, analysts, and professionals to define successful and economical business enterprise instruction techniques in pesantren. Tending to challenges such as constrained writing and program maintainability will improve the quality and pertinence of business instruction, cultivating financial strengthening inside pesantren communities and contributing to Indonesia's financial improvement. The discoveries emphasize the significance of proceeded investigate and collaboration to encourage development enterprise instruction in pesantren and its broader affect on Indonesian society.